"As Raízes da Ética: conferência no Instituto Gramsci (maio de 1964)", de Jean-Paul Sartre - Thierry Lacour, Philippe Claude; Oliveira Chaia, Jade; Oliveira Franca, Igor; de Paula Gonçalves Barbosa, Luiz Guilherme; Mucury Teixeira, Manuella; Vargas de Toledo, Marcelo; de Magalhães Chagas, Marcos Vinícius; Alves Teixeira, Michelly; Randal e Zitti, Sèdjro Crédo; Guimarães Correa, Silvana Maria; Caprio Leite de Castro, Fábio; Jacques Wormser, Gérard Lucien (Revista de Filosofia Moderna e Contemporânea, 2018)
Tradução